JmjC ‐domain‐containing histone demethylases - Højrup, C; Coleman, OD; Bukowski, J-P; Clausen, RP; Kawamura, A (Wiley, 2019)
Histone lysine demethylases (KDMs) play a pivotal role in the epigenetic modulation of higher order chromatin structure and transcriptional activity in eukaryotic cells by regulating the methylation states on histones. KDMs are involved in fundamental cellular processes such as proliferation, differentiation, genome integrity, and development. This chapter provides an overview of the Jumonji C (JmjC)‐domain‐containing KDM family, with a particular focus on their therapeutic potential and the recent progress in the development of JmjC‐KDM inhibitors. It overviews the different inhibitor development strategies employed for targeting the JmjC domain of KDMs and highlights some of the subfamily‐targeted inhibitors reported to date. Due to the different domain architectures between each subfamily, as well as greater diversity between the reader domains than between their respective JmjCs, it offers better opportunities for achieving selectivity.